THE CHALLENGE OF USING VIRTUAL LEARNING IN LEARNING ENGLISH AT SMKN 3 TORAJA UTARA - Pratiwi bela, Irene; Labiran, Roni (Publikasi dan UKI Press UKI Toraja., 2024)
The purpose of this study is to find out the level of interest of students in learning English in the implementation of the Merdeka Curriculum. This study used descriptive quantitative methods. The researcher used cluster sampling to chose one of the as classes of the object of study. The instruments used for data collection are observation and questionnaire to find out students' interests. Data analysis shows that fifth grade students of SDN 8 Makale have an interest in learning English. This can be seen from the data obtained from statements 1-20 which shows that from the results of the average student answer score is 81% and can be categorized on high criteria. Based on the result of data analysis, researcher concludes that grade V students of SDN 8 Makale have a high interest in learning English.